Diseño y construcción de un dispositivo funcional para el pegado de sistemas microfluídicos (2020)
Smart industries laboratory located in Universidad de los andes design and manufacture low cost fluidic microsystems for their own purpose. The document show the design and creation step by step of a functional prototype for the correct pasting of these microsystems using electronic devices widely used in electronic instrumentation projects. As a microcontroller was used an Arduino Mega along with the RAMPS 1.4 board commonly used in low cost 3d printers. To make the project a reality it was created a completely new firmware capable of controlling parameters such as temperature, pressure and time using two different types of intuitive interfaces. The first and principal interface is the interaction of the user with the device using an LCD and a rotary encoder with the possibility to use this interface on two languages (Spanish and English). The second interface is a unique remote desktop app developed entirely on JAVA. The result of the project is a functional prototype that fulfil its purpose of pasting microfluidic systems developed in the Smart industries lab in an intuitive way which allow anyone with no knowledge on these fluidic systems to paste them using this prototype.--Taken from the Degree Document Format.